Jerome A. Stone’un Minimal Aşkınlık Modeli - Elif Ünlü (Din ve Bilim Muş Alparslan Üniversitesi İslami İlimler Fakültesi Dergisi)
Jerome A. Stone is one of the philosophers of religion who works on religious naturalism. He stands out with his defense of a minimalist understanding of religion in religious naturalism. In this article, Stone's minimal model of transcendence in religious naturalism is examined and evaluated. First, Stone's idea of religious naturalism is explained, then the minimal model of transcendence is discussed. In terms of his philosophy, Stone basically draws attention to the importance of nature in human life. By accepting nature as transcendent and sacred, it emphasizes the reinterpretation of nature in a way that will affect all our beliefs and thoughts. According to him, nature also plays an effective role in thoughts about God. Stone's approach to nature as a transcendent and religious aspect constitutes the founding elements of his minimalist understanding of religion. Stone rejects any metaphysical divinity and defends a naturalistic understanding of religion that emphasizes nature. He thinks that this view is a good alternative for those who do not want to choose theism or atheism. In the minimal model, the qualities of power and goodness in the personal God are attributed to the divinity in nature. According to Stone, the minimal model meets the spiritual needs in life while also providing a naturalistic philosophy with a non-metaphysical God in this world. He argues that he offers an alternative understanding of religion by softening the strict divinity of theism with a concept of God that can be defended within a naturalistic framework, rather than a concept of God that includes metaphysical elements. Stone argues that the minimal model of transcendence may not be satisfactory for everyone, but it can be a religious alternative for those who want to gain the transcendent dimension in life. The Minimal model of transcendence basically tries to preserve the concept of transcendence in nature, and, on the other hand, it explains the nature and this world without exceeding the ontological limits in the experiences of transcendence or by preserving the limits in claims that cannot be proven naturalistically. In Stone's minimal model of transcendence in religious naturalism, openness to the possibilities that will occur is important. The main problem for Stone's naturalistic perspective is whether the object of religious orientation is the whole of nature or a part of it. If it is a part of the universe, it is a creative process within the universe or the sum of creative elements. In terms of religious naturalism, it is necessary to redefine how the concept of God is conceived within a naturalist framework in minimal thought, centered on nature, and beyond the traditional meaning of this concept. In Stone's minimal model of transcendence, it can be said that the God-nature-human relationship is transferred to the nature-human relationship by attributing sacredness to nature. In Stone's understanding of religion, there is the problem of which divine qualities the object of non-metaphysical religious orientation will have. The article discusses what kind of a being nature is, what the divine powers in nature are, and the possibility of creating a religious understanding without defending any concept of God in a minimal religious understanding. In addition, the compatibility of various understandings of God with minimal religious naturalism and what it means to be religious in a minimal religious understanding are evaluated.